Red Light Means Stop! Teaching Theology through Exposure Learning in Manila's Red Light District - Mercer, Joyce Ann (Teaching theology and religion, 2002)
This paper explores exposure learning as a strategy for teaching theology in a Christian seminary, by describing and analyzing one multicultural Asian class's exposure to the “Red Light Districts” of Manila (Philippines). Exposures consist of short-term experiential learning events through participation and immersion into a specific context, preceded and followed by a process of study and reflection. Exposure learning has the potential to minimize certain forms of student resistance around emotionally-charged subjects, such as the integration of race, class, and gender into theological education, because it is the experience together with shared critical reflection on it and not the teacher's viewpoints per se that unsettle prior interpretive frameworks. Exposure learning also carries certain risks and ethical dilemmas, and its long-term effects on transformation remain unclear. In spite of these pedagogical issues which the paper explores in detail, the paper supports exposure learning as an alternative experiential form of education for transformation.